2018
DOI: 10.1002/dmrr.3047
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic variability in the development of cardiovascular complications in diabetes

Abstract: Diabetes mellitus represents a major risk factor for the development of coronary artery disease and other vascular complications. Glycated haemoglobin, fructosamine, and fasting blood glucose levels are partial parameters to exhaustively describe patient dysglycemic status. Thus, recently the new concept of glycemic variability has emerged, including information about two major aspects: the magnitude of blood glucose excursions (from nadir to peak, thus lower and higher spikes) and the time intervals in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 97 publications
1
114
0
Order By: Relevance
“…Further, nonexercise physical activity can aid in prevention and treatment of type 2 diabetes [19]. Both sustained hyperglycemia and large glucose fluctuations adversely affect cardiovascular health of diabetic subjects [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, nonexercise physical activity can aid in prevention and treatment of type 2 diabetes [19]. Both sustained hyperglycemia and large glucose fluctuations adversely affect cardiovascular health of diabetic subjects [20].…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of time spent in hyperglycemia is important, since microvascular and macrovascular complications and proinflammatory phenotype in diabetes have been shown from chronic sustained hyperglycemia and acute glycemic fluctuations [20,32]. While there are strong grounds to con-tinue to emphasize importance of regular aerobic and muscle-strengthening activities to prevent and manage type 2 diabetes, JD offers a solution to negate the adverse glycemic effects of high amounts (i.e., hours) of sitting in the adult population.…”
mentioning
confidence: 99%
“…Glycemic variability from target range, a complex phenomenon of intraday and interday glucose fluctuations, as well as time in range has emerged as strong measures for assessing glycemic control in addition to HbA1c. [34][35][36][37] Glycemic variability is an independent risk factor for diabetic complications 38 and is often expressed as standard deviation, coefficient of variation/variance, mean amplitude glycemic excursion, and a host of other metrics. Postmeal glucose excursions largely contribute to the intraday glycemic variability and can be more effectively managed using prandial doses of rapid-acting insulin analogues.…”
Section: Glycemic Variabilitymentioning
confidence: 99%
“…36,78 Another 1-year study found the low-carbohydrate diet resulted in decreased glucose variability, which has been found to be an independent CVD risk factor, making it an important overall consideration. 85 An isocaloric trial found the low-carbohydrate arm had a significant decrease in insulin and visceral fat accumulation compared to a high-carbohydrate arm. 70 Of the 10 studies that reported on lipids, five found significant improvements in triglycerides with a low-carbohydrate diet 74,78,[82][83][84] ;…”
Section: Summary Of Evidencementioning
confidence: 99%